Gallic Acid in Ayurvedic Herbs and Formulations - Tekale3, V.U. Borde1*, P.P. Pangrikar2; S.U. (Recent Research in Science and Technology, 2011)
Thirty Ayurvedic herbs and formulations have been screened for the presence of gallic acid by the use of silica gel thin layer chromatography. The samples showing presence of gallic acid in screening by the silica gel thin layer chromatography were quantitatively analyzed for gallic acid by ferric reducing antioxidant power (FRAP) assay. The water extracts of nine samples out of thirty were found to contain gallic acid by TLC. All these samples contain a good amount of gallic acid with Amla 27.36mg/g ranking first followed by Triphala 18.24mg/g. The results demonstrated rich sources of gallic acid in some ayurvedic herbs and formulations, which might provide new light on uses of this medicinally important compound.